A atenção à saúde na assistência estudantil nas universidades federais do Nordeste - Carvalho, Emmanoel Ferreira (2022)
The objectives of the National Student Assistance Policy, as an instrument for the materialization of the social right to social assistance and education, is to provide the necessary resources to mitigate obstacles throughout the university course, allowing students to develop during graduation, reducing the percentage of dropout and enrollment cancellations. The National Student Assistance Program (PNAES) was established by Decree No. 7,234/2010 and, among its objectives, is to minimize the effects of social inequalities. The Decree establishes that the IFES offer actions in different areas, including health. This research focuses on the actions in health care available to undergraduates. With reference to the V Survey of Socioeconomic and Cultural Profile of Undergraduates from Federal Institutions of Higher Education in 2018, developed by the National Forum of Deans of Community and Student Affairs - a survey was carried out on the health care actions developed within the scope of the Federal Universities of the Northeast in 2019. The research methodology is based on the proposal of Laurence Bardin (2011) with an analytical perspective of the content obtained with the interview questionnaires submitted to the Universities investigated through the FalaBR information access site. The results indicated a lack of articulation between the Deans of Extension and Student Assistance and the respective courses in the health area of the IFES analyzed in the offer of health actions, initiatives and projects, as well as few initiatives of well-being actions available. to students and overload of demands for Psychology services. As a proposition, the author recommended a draft resolution for the creation of an internal network of intersectoral health care, instituting a student passport for the purpose of registering demands.